Gene profiling reveals a contact allergy signature in most positive Amerchol L‐101 patch test reactions. (25th March 2022) - Ljungberg Silic, Linda; Lefevre, Marine‐Alexia; Bergendorff, Ola; De Bernard, Simon; Nourikyan, Julien; Buffat, Laurent; Nosbaum, Audrey; Bruze, Magnus; Nicolas, Jean‐François; Svedman, Cecilia; Vocanson, Marc
Abstract: Background: Diagnosis of contact allergy (CA) to Amerchol L‐101 (AL‐101), a marker for lanolin allergy, is problematic. Positive patch test reactions are frequently doubtful or weakly positive and difficult to associate with clinical relevance. Objective: To gain further insight on the allergic or irritant nature of skin reactions induced by AL‐101 patch test. Methods: We re‐tested in a dose–response fashion, 10 subjects with AL‐101 CA and performed comprehensive transcriptomic analysis (gene arrays, quantitative real‐time polymerase chain reaction [qRT‐PCR]) of samples of their skin reactions. Results: Eight of the 10 CA subjects reacted positively upon re‐test, whereas two did not react. Most of AL‐101 positive patch tests expressed an allergy signature with strong activation of gene modules associated with adaptive immunity and downregulation of cornification pathway genes. In addition, the breadth of gene modulation correlated with the magnitude of patch test reactions and the concentration of AL‐101 applied. However, we observed that some of the positive patch test reactions to AL‐101 expressed no/few allergy biomarkers, suggesting the induction of an irritant skin inflammation in these samples. Conclusions: This study confirms that AL‐101 is an allergen that can cause both contact allergy and contact irritation. Our results also highlight that molecular profiling might help to strengthen clinical diagnosis. Abstract : Diagnosis of contact allergy to lanolin by patch testing with Amerchol L‐101 (AL‐101) is often questionable due the irritant and/or allergic properties of AL‐101. An allergy signature was detected in most, but not all, patients with patch test reactions to AL‐101, with a significant correlation between the breadth of gene modulation and the clinical reaction or the AL‐101 concentration. Molecular profiling approaches might be of major value to interpret weakly positive patch test reactions to AL‐101, and to help clinicians to refine the diagnosis of contact allergy to lanolin.